Integrating Conflicting Goals of the EC Water Framework Directive and the EC Habitats Directives Into Floodplain Restoration Schemes - Weigelhofer, Gabriele; Feldbacher, Eva; Trauner, Daniel; Pölz, Eva; Hein, Thomas; Funk, Andrea (Frontiers in Environmental Science, 2020)
River floodplains are among the most threatened ecosystems of the world and their protection and restoration is of key importance for river managers. In Europe, the Water Framework Directive (WFD) and the Habitats and Birds Directives (HBDs) provide a guideline for decision processes in floodplain restoration projects. While the WFD, however, represents an aggregated, multiple-species approach aiming at the restoration of the natural hydrological dynamics, the single-species focused HBDs regulate the protection of the existing fauna and flora with protection status. Thus, trade-offs between rheophilic and stagnophilic aquatic organisms may hamper the definition of a compromise solution between the ecological objectives of the restoration. We present an assessment scheme for the restoration of a degraded Danube floodplain near Vienna, which equally considers both WFD and HBDs objectives in a transparent, comprehensible, and objective way. In a first step, predictive hydrological and ecological models were generated for different hydrological scenarios considering the aquatic community composition (floodplain index according to WFD) as well as individual protected species of the taxonomic groups fish, amphibians, reptiles, and water birds (HBDs). Based on these models, we developed an assessment scheme which considered potential changes in the available habitats, the current conservation states, and priorities of the species. Thereby, we included experiences from other restoration projects. The results show that both the multiple-species and the single-species approach achieved a similar ranking of the hydrological scenarios, in which the “business-as-usual” alternative without any restoration measure was identified as the worst case. The multiple-species approach of the floodplain index provided a clear ranking of the hydrological scenarios and revealed a low potential of any target measure to restore the pre-regulation state of the floodplain. In contrast, the single-species approach required a much higher degree of decisions by experts, but provided a detailed insight into spatial effects of the measures on different species, thus revealing the potential for local compensation measures. Our study demonstrates that a combination of these two approaches can be an effective tool for river managers in the development of sustainable floodplain restoration schemes in accordance with the WFD, the HBDs, and national nature protection laws (in this case, the Nature Conservation Acts of Vienna and Lower Austria).